CO2 corrosion resistant oil casing and preparation method thereof

By using scrap steel to prepare CO2 corrosion-resistant oil casing, the problem of high preparation cost and insufficient CO2 corrosion resistance of existing nickel and molybdenum-based alloy materials is solved, and low-cost and high-performance oil casing materials are achieved.

CN119640150APending Publication Date: 2025-03-18DALIPAL PIPE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411952346.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing nickel and molybdenum-based alloy oil casing materials are costly to prepare, but after reducing the cost, its anti-CO2 corrosion ability is difficult to meet the ultra-deep well mining needs.

Method used

Using scrap steel as raw material, anti-CO2 corrosion-resistant oil casing is prepared through electric furnace smelting, alloying refining, vacuum treatment and continuous casting processes. In specific steps, the feeding order of alloying refining is adjusted to improve alloy yield and composition uniformity.

Benefits of technology

It has achieved low-cost prepared anti-CO2 corrosion oil casing, with excellent anti-CO2 corrosion performance, and can meet the needs of ultra-deep well mining.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640150A_ABST
    Figure CN119640150A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of oil casing materials, in particular to a CO2 corrosion resistant oil casing and a preparation method thereof. The CO2 corrosion resistant oil casing comprises the following chemical components in percentage by mass: 0.13% < = C < = 0.16%, 0.20% < = Si < = 0.30%, 0.55% < = Mn < = 0.65%, 2.9% < = Cr < = 3.1%, 0.3% < = Mo < = 0.4%, 0.02% < = Al < = 0.04%, 0.008% < = P, 0.0015% < = S, < = 2ppm of [H], < = 15ppm of [O], < = 60ppm of [N] and the balance of Fe and inevitable impurities. The problems that in the prior art, the preparation cost of a nickel-molybdenum-based alloy oil casing material is high, but the CO2 corrosion resistance of the oil casing material cannot meet the ultra-deep well mining requirement after the cost is reduced are effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of oil casing material preparation, and in particular to a CO 2 Corroded oil casing and preparation method thereof. Background Art

[0002] Due to the severe global oil supply situation and the stimulation of oil prices, some oil and gas fields with very harsh geological and environmental conditions, including those in severe corrosive environments, have been developed one after another, and new drilling and completion technologies and processes have been put into use one after another, resulting in the increasingly complex and harsh service conditions of oil well pipes. 2 The development of a series of pipes is one of them.

[0003] At present, more and more deep and ultra-deep well oil and gas resources are being developed at home and abroad. The annual growth rate of deep well development of PetroChina over 6,000 meters is 25%. During the deep well drilling and completion process, the casing is very likely to fail under the combined effects of complex stress, temperature and pressure. Under high strength conditions, high toughness ensures that the casing has better service safety. Currently, nickel and molybdenum-based alloy oil casing are widely used for mining and contain CO 2 Nickel and molybdenum based alloy casing has good resistance to CO 2 The corrosion resistance of low alloy oil casing is good, but the price is high, which limits the widespread use of such materials. Although the cost can be reduced by reducing the alloy content, the resistance of the resulting low alloy oil casing to CO 2 The corrosion performance will also decline, making it difficult to meet the mining needs of ultra-deep wells.

[0004] Therefore, it is necessary to develop a low-cost, CO 2 Corrosion-resistant oil casing materials with strong resistance to corrosion and sulfide stress corrosion have great practical significance for oil well exploitation. Summary of the invention

[0005] The preparation cost of nickel and molybdenum-based alloy oil casing materials in the existing technology is relatively high, but after reducing the cost, the CO resistance of oil casing materials can be improved. 2 The corrosion resistance is difficult to meet the demand of ultra-deep well mining. The present invention provides a CO 2 Corrosion-resistant oil casing and its preparation method. 2 The oil casing has excellent resistance to CO 2 It has good corrosion resistance, can meet the needs of ultra-deep well mining, and has low preparation cost. It is made from scrap steel as raw material, providing new ideas for the development of oil casing.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The first aspect of the present invention provides an anti-CO 2Corrosion of oil casing, the anti-CO 2 The raw materials of corroded oil casing include the following chemical components in mass percentage: 0.13%≤C≤0.16%, 0.20%≤Si≤0.30%, 0.55%≤Mn≤0.65%, 2.9%≤Cr≤3.1%, 0.3%≤Mo≤0.4%, 0.02%≤Al≤0.04%, P≤0.008%, S≤0.0015%, [H]≤2ppm, [O]≤15ppm, [N]≤60ppm, and the balance is Fe and unavoidable impurities.

[0007] The present invention designs a method having good resistance to CO 2 Corroded oil casing, the presence of carbon can improve the strength and hardness of steel, and also affect the toughness of steel. When the carbon content is high, the toughness of steel will decrease; when the carbon content is too high, it will increase the brittleness of steel; the right amount of carbon content will also improve the wear resistance of steel, which can meet the needs of various application scenarios of oil casing. The addition of silicon can significantly improve the yield strength and tensile strength of steel, and can also effectively remove samples in molten steel and reduce defects such as bubbles in steel, thereby improving the quality and density of steel, making steel able to effectively resist CO 2 Corrosion. Manganese can improve the strength and hardness of steel, and also has the effect of deoxidation and desulfurization, reducing the porosity of steel and improving the density of steel. Chromium can form a stable and dense oxide film on the surface of steel (mainly Cr 2 O 3 ), which can effectively prevent the chemical reaction between steel and the surrounding medium, making the steel have good corrosion resistance. Molybdenum can form fine special carbides in steel. These carbides are dispersed in the steel matrix, playing a strengthening role, thereby significantly improving the corrosion resistance of steel and effectively slowing down the corrosion rate of steel. The addition of aluminum can refine the grains of steel, prevent grain growth, improve the strength and toughness of steel, and at the same time form a layer of aluminum oxide protective film on the surface of steel to prevent oxygen from further contacting the inside of the steel, playing an anti-corrosion role.

[0008] The second aspect of the present invention provides the anti-CO 2 The preparation process of corroded oil casing includes the following steps: The steel-making raw materials are subjected to an electric furnace smelting process, an alloying refining process, a VD vacuum treatment process, and a continuous casting process to obtain a cast billet; the cast billet is sequentially subjected to a heating process, a rolling process, and a heat treatment process to obtain a CO resistant 2 Corrosion of oil casing; The specific operation of the alloying refining process is as follows: in an inert atmosphere, when the molten steel obtained by electric furnace smelting reaches 4%-6%, a pre-deoxidizer is added to the ladle; when the molten steel reaches 14%-16%, a metal deoxidizer is added to the ladle; when the molten steel reaches 24%-26%, a chromium-containing alloy is added to the ladle for the first alloying treatment for 50-60s, and the tapping is completed to obtain a first alloyed molten steel; A diffusion deoxidizer, a low-carbon ferrochrome and a slag-forming agent are sequentially added to the primary alloyed molten steel for secondary alloying treatment to obtain a secondary alloyed molten steel; and the low-carbon ferrochrome in the secondary alloyed molten steel is refined to obtain a refined molten steel and slag.

[0009] Compared with the prior art, the present invention adopts a three-step alloying and refining process. The inventor has found through a large number of creative experiments that in the second alloying and refining process, the order of adding low-carbon ferrochrome has a crucial influence on the quality of the refined steel liquid. If the feeding method of slag-making agent-deoxidizer-low-carbon ferrochrome is adopted, the yield of Cr in low-carbon ferrochrome will be only about 85%, and the composition will be uneven. This is because the amount of top slag of the slag-making agent added first is large, the slag layer is large, and the slag is thick. After the low-carbon ferrochrome is added, it is easy to accumulate on the surface of the slag, and the alloy surface is wrapped with refined slag, which will cause the alloy to be difficult to melt, thereby reducing the yield of the alloy. The present invention adjusts the feeding order, and feeds in the order of deoxidizer-low-carbon ferrochrome-slag-making agent, which effectively improves the yield of the alloy, especially the yield of Cr, which is increased to more than 97%, and the composition is uniform, thereby effectively improving the corrosion resistance of the steel.

[0010] Preferably, the steel tapping endpoint in the electric furnace smelting process is [P]≤0.005%, and the target temperature is 1620°C-1640°C.

[0011] The present invention limits the tapping end temperature, which can effectively avoid the rephosphorization of molten steel due to excessively high temperature in the later stage of smelting, thereby affecting the performance of the steel. At the same time, the present invention controls the content of [P] in the molten steel to below 0.005%, which can further improve the low-temperature impact performance of the steel.

[0012] Preferably, the pre-deoxidizer is silicon carbide.

[0013] Further preferably, the silicon carbide meets the requirements of C≤10%, SiC≥80%, H 2 Requirements of O≤0.5%, S≤0.25% and P≤0.06%.

[0014] Preferably, the metal deoxidizer is an aluminum block.

[0015] Further preferably, the mass percentage of Al in the aluminum block is ≥97.5%.

[0016] Preferably, the diffusion deoxidizer is aluminum particles and calcium carbide in a mass ratio of 1:1.5-1:2.

[0017] Further preferably, the mass percentage of Al in the aluminum particles is ≥97.5%, the diameter is 8-10 mm, and the length is 20-30 mm.

[0018] Further preferably, the calcium carbide CaC 2 The mass percentage is ≥80%, and the gas generation volume is ≥275L / kg.

[0019] Preferably, the chromium-containing alloy comprises the following raw material components in percentage by mass: 54.5%-56.8% low-carbon ferrochrome, 12.3%-13.6% high-carbon ferrochrome, 11.1%-11.4% ferromolybdenum and 19.8%-20.5% silicon-manganese alloy.

[0020] Preferably, the carbon content of the low carbon ferrochrome is 0.02%-0.1%.

[0021] Preferably, the slagging agent is lime.

[0022] Preferably, the Cr in the slag 2 O 3 The mass percentage is 0.1%-0.5%.

[0023] Preferably or further preferably, the mass ratio of the added amount of the pre-deoxidizer to the molten steel is 0.47:1000-0.48:1000.

[0024] Preferably or further preferably, the mass ratio of the added amount of the metal deoxidizer to the molten steel is 1.64:1000-1.65:1000.

[0025] Preferably or further preferably, the mass ratio of the added amount of the chromium-containing alloy to the molten steel is 40.5:1000-44:1000.

[0026] Preferably or further preferably, the mass ratio of the added amount of the low carbon ferrochrome to the primary alloyed steel liquid is 17:1000-23:1000.

[0027] Preferably or further preferably, the mass ratio of the added amount of the low carbon ferrochrome to the secondary alloyed steel liquid is 4:1000-6:1000.

[0028] Preferably or further preferably, the mass ratio of the added amount of the diffusion deoxidizer to the molten steel is 0.85:1000-0.95:1000.

[0029] Preferably or further preferably, the mass ratio of the added amount of the slag-forming agent to the molten steel is 8:1000-9:1000.

[0030] Preferably, the specific operation of the secondary alloying treatment is: power on, immediately add part of the diffusion deoxidizer to the primary alloyed molten steel for refining for 1 min-2 min, then add low-carbon ferrochrome, the remaining diffusion deoxidizer and slag-forming agent and continue refining for 10 min-12 min, take samples for testing, and obtain the secondary alloyed molten steel.

[0031] Further preferably, the partial diffusion deoxidizer accounts for 20%-24% of the total mass of the diffusion deoxidizer.

[0032] Preferably, in the VD vacuum treatment process, when the vacuum degree is 10kPa-100kPa, the argon blowing amount is 50NL / min-80NL / min; when the vacuum degree is 5kPa-10kPa, the argon blowing amount is 80NL / min-120NL / min; when the vacuum degree is 500Pa-5kPa, the argon blowing amount is 120NL / min-160NL / min; when the vacuum degree is 67Pa-500Pa, the argon blowing amount is 160NL / min-200NL / min; when the vacuum degree is ≤67Pa, first keep the argon blowing amount at 200NL / min-220NL / min for 10min-12min, and then reduce the argon blowing amount to 100NL / min-120NL / min and keep it for 3min-5min.

[0033] Preferably, the continuous casting process adopts secondary cooling with electromagnetic stirring of the crystallizer and electromagnetic stirring at the end, wherein the flow rate of the primary cooling water is 4.6m 3 / t-5.1m 3 / t, the secondary cooling water flow rate is 0.32m 3 / t-0.34m 3 / t, the crystallizer electromagnetic stirring current is 400A-450A, the frequency is 3Hz-5Hz, the end electromagnetic stirring current is 350A-400A, the frequency is 7Hz-9Hz, the superheat is 20℃-25℃, and the pulling speed is 1.5m / min-2.1m / min.

[0034] Preferably, the heating procedure of the heating process is as follows: the temperature of the preheating section is 700℃-900℃, and the holding time is 20min-30min; the temperature of the first heating section is 900℃-1200℃, and the holding time is 30min-40min; the temperature of the second heating section is 1200℃-1280℃, and the holding time is 30min-40min; the temperature of the third heating section is 1220℃-1300℃, and the holding time is 30min-40min; the temperature of the equalizing section is 1220℃-1290℃, and the holding time is 20min-30min.

[0035] Preferably, the rolling process includes a perforation process, a rolling process, a diameter reducing process, a cooling bed process, a straightening process and a flaw detection process in sequence; wherein, in the rolling process, the length of the concentrated deformation section of the roller is 28mm-32mm, the feed angle is 6.9°-7.1°, the rolling angle is 11.8°-12.2°, the guide disc speed is 1.5m / s-1.6m / s, and the rolled piece linear speed is 0.40m / s-0.42m / s.

[0036] Preferably, the heat treatment includes quenching, water cooling, tempering, straightening, air cooling and flaw detection in sequence; wherein the quenching temperature is 810°C-910°C, and the tempering temperature is 650°C-708°C.

[0037] Further preferably, during the quenching operation, the quenching temperature of the heating section is 810°C-850°C, and the quenching holding time of the heating section is 35min-60min; the quenching temperature of the soaking section is 890°C-910°C, and the quenching holding time of the soaking section is 16min-24min.

[0038] Further preferably, during the tempering operation, the tempering temperature of the first heating stage is 650°C-690°C, and the tempering holding time of the first heating stage is 20min-30min; the tempering temperature of the second heating stage is 688°C-708°C, and the tempering holding time of the second heating stage is 15min-30min; the tempering temperature of the soaking stage is 890°C-910°C, and the tempering holding time of the soaking stage is 30min-40min. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 The anti-CO obtained in Example 1 2 Metallographic structure diagram of corroded oil casing; Figure 2 The anti-CO obtained in Example 2 2 Metallographic structure diagram of corroded oil casing; Figure 3 The anti-CO obtained in Example 3 2 Metallographic structure diagram of corroded oil casing; Figure 4The anti-CO obtained in Comparative Example 1 2 Metallographic structure diagram of corroded oil casing; Figure 5 The anti-CO obtained in Comparative Example 2 2 Metallographic structure diagram of corroded oil casing; Figure 6 The anti-CO obtained in Comparative Example 3 2 Metallographic structure diagram of corroded oil casing; Figure 7 The anti-CO obtained in Example 1 2 Inclusion test results of corroded oil casing; Figure 8 The anti-CO obtained in Comparative Example 1 2 Inclusion test results of corroded oil casing; Fig. 9 The anti-CO obtained in Comparative Example 2 2 Inclusion test results of corroded oil casing; Fig.10 The anti-CO obtained in Comparative Example 2 2 Inclusion test results of corroded oil casing. DETAILED DESCRIPTION

[0040] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] Example 1 This embodiment provides an anti-CO 2 Corroded oil casing and its preparation method, specifically including the following contents: Ingredients: 58.48t scrap steel, 25.8t briquettes and 1.5t graphite balls; The first batch of materials: 22.36t of scrap steel as base, 13.76t of briquettes on top, and 1t of graphite balls on top; The second batch of materials: 18.92t of scrap steel as base, 10.32t of briquettes on top, and 0.5t of graphite balls on top; The third batch of materials: 17.2t of scrap steel as base and 1.72t of briquettes on top; The carbon content of graphite balls is ≥77%, and the bulk density of each batch is 0.8t / m 3 .

[0042] Step 1, add the first batch of materials into the electric arc furnace, supply power for smelting for 12 minutes, and add 1500kg of lime; when the first batch of materials is 85% melted, add the second batch of materials, continue smelting for 9 minutes, and add 320kg of lime; when the secondary material is 80% melted, add the third batch of materials, continue smelting for 17 minutes, when the slag basicity is 3 and the mass percentage of FeO in the slag is 17%, perform slag flow operation; when the furnace temperature is 1630℃ and the mass percentage of [P] in the molten steel is less than 0.005%, tapping is performed under an inert atmosphere; Step 2, under an inert atmosphere, when the steel tapping amount reaches 5%, 42.5 kg of silicon carbide is added to the ladle; when the steel tapping amount reaches 15%, 147.6 kg of aluminum block is added to the ladle; when the steel tapping amount reaches 25%, a chromium-containing alloy is added to the ladle for the first alloying treatment for 60 seconds, and the steel tapping is completed to obtain a primary alloyed steel liquid; wherein the chromium-containing alloy includes the following raw material components in percentage by weight: 55.3% low-carbon ferrochrome, 13.1% high-carbon ferrochrome, 11.2% ferromolybdenum and 20.4% silicon-manganese alloy; Under the inert atmosphere, the primary alloyed steel liquid is sent into the LF refining furnace, and power is supplied. 6.5 kg of aluminum particles and 12.3 kg of calcium carbide are immediately added to the primary alloyed steel liquid for refining for 2 min, and then 1700 kg of low-carbon ferrochrome, 22 kg of aluminum particles, 41.5 kg of calcium carbide and 722 kg of lime are added for further refining for 12 min, and sampling is performed to obtain the secondary alloyed steel liquid; The LF refining furnace was turned on for power supply, and 425 kg of low-carbon ferrochrome was added to the secondary alloyed molten steel for further refining for 8 min, and samples were taken for testing; when the [Cr] content was 2.97%, the power supply was stopped to obtain refined molten steel and slag; Step 3, the refined molten steel is subjected to vacuum treatment in the VD station. When the vacuum degree is 10kPa-100kPa, the argon blowing amount is 75NL / min; when the vacuum degree is 5kPa-10kPa, the argon blowing amount is increased to 100NL / min; when the vacuum degree is 500Pa-5kPa, the argon blowing amount is increased to 140NL / min; when the vacuum degree is 67Pa-500Pa, the argon blowing amount is increased to 180NL / min; when the vacuum degree is ≤67Pa, the argon blowing amount is first maintained at 230NL / min for 11min and then reduced to 110NL / min for 5min; vacuum-treated molten steel is obtained; Step 4: The vacuum treated molten steel is cast at a constant speed by using secondary cooling combined with electromagnetic stirring of the crystallizer and terminal battery stirring, wherein the primary cooling water flow rate is 4.8m 3 / t, the secondary cooling water flow rate is 0.33m 3 / t, the crystallizer electromagnetic stirring current is 420A, the frequency is 4Hz, the end electromagnetic stirring current is 370A, the frequency is 8Hz, the superheat is 25℃, and the pulling speed is 1.7m / min; the Φ200mm casting billet is obtained; Step 5, the Φ200mm ingot is sent into the annular furnace for heating, and the heating program is set as follows: the preheating section temperature is 800℃, and the holding time is 25min; the heating section temperature is 1100℃, and the holding time is 35min; the heating section temperature is 1250℃, and the holding time is 35min; the heating section temperature is 1280℃, and the holding time is 35min; the soaking section temperature is 1280℃, and the holding time is 25min; the heated ingot is pierced and rolled by a continuous rolling mill, and the length of the concentrated deformation section of the roll in the rolling process is set to 28mm, the feeding angle is 7.0°, the rolling angle is 12.0°, the guide disc speed is 1.55m / s, and the rolled piece linear speed is 0.41m / s; the hot-rolled steel pipe after rolling is subjected to micro-tension reduction, straightened while hot, and air-cooled on a cooling bed, and enters the heat treatment process after passing the flaw detection; Step 6: Send the qualified steel pipe after flaw detection into the heating furnace for quenching treatment, wherein the quenching temperature of the heating section is 830℃, and the heat preservation is 45min, and the quenching temperature of the soaking section is 900℃, and the heat preservation is 20min; after quenching, the steel pipe is water-cooled to 80℃ by external spraying and internal spraying, and then sent to the heating furnace for tempering treatment, wherein the tempering temperature of the heating section is 670℃, and the heat preservation is 25min, the tempering temperature of the heating section is 698℃, and the heat preservation is 20min, and the tempering temperature of the soaking section is 900℃, and the heat preservation is 35min; after tempering, the steel pipe is straightened while hot, and put into the cooling bed for air cooling. After the flaw detection is qualified, the steel pipe is resistant to CO 2 Corrosion of oil casing.

[0043] After testing, the anti-CO 2 The raw materials of corroded oil casing include the following chemical components in mass percentage: C: 0.14%, Si: 0.26%, Mn: 0.61%, Cr: 2.97%, Mo: 0.33%, Al: 0.03%, P: 0.007%, S: 0.0012%, [H]: 1.2ppm, [O]: 11ppm, [N]: 50ppm, and the balance is Fe and unavoidable impurities.

[0044] Example 2 This embodiment provides an anti-CO 2 Corroded oil casing and its preparation method, specifically including the following contents: Ingredients: 59.5t scrap steel, 24.65t briquettes and 1.53t graphite balls; The first batch of materials: 22.1t of scrap steel as base, 13.6t of briquettes on top, and 1.02t of graphite balls on top; The second batch of materials: 19.55t of scrap steel as base, 9.35t of briquettes on top, and 0.51t of graphite balls on top; The third batch of materials: 17.85t of scrap steel as base and 1.7t of briquettes on top; The carbon content of graphite balls is ≥77%, and the bulk density of each batch is 0.9t / m 3 .

[0045] Step 1, add the first batch of materials into the electric arc furnace, supply power for smelting for 12 minutes, and add 1550kg of lime; when the first batch of materials is 85% melted, add the second batch of materials, continue smelting for 9 minutes, and add 380kg of lime; when the secondary material is 80% melted, add the third batch of materials, continue smelting for 17 minutes, when the slag basicity is 2.5 and the mass percentage of FeO in the slag is 16%, perform slag flow operation; when the furnace temperature is 1625℃ and the mass percentage of [P] in the molten steel is less than 0.005%, tapping is performed under an inert atmosphere; Step 2, under an inert atmosphere, when the steel tapping amount is 5%, 41.8 kg of silicon carbide is added to the ladle; when the steel tapping amount is 15%, 143.5 kg of aluminum block is added to the ladle; when the steel tapping amount is 25%, a chromium-containing alloy is added to the ladle for the first alloying treatment for 55 seconds, and the steel tapping is completed to obtain a primary alloyed steel liquid; wherein the chromium-containing alloy includes the following raw material components in percentage by weight: 55.3% low-carbon ferrochrome, 13.1% high-carbon ferrochrome, 11.2% ferromolybdenum and 20.4% silicon-manganese alloy; Under the inert atmosphere, the primary alloyed steel liquid is sent into the LF refining furnace, and power is supplied. 6.5 kg of aluminum particles and 12.3 kg of calcium carbide are immediately added to the primary alloyed steel liquid for refining for 2 min, and then 1700 kg of low-carbon ferrochrome, 22 kg of aluminum particles, 41.5 kg of calcium carbide and 722 kg of lime are added for further refining for 12 min, and sampling is performed to obtain the secondary alloyed steel liquid; The LF refining furnace was turned on to supply power, and 425 kg of low-carbon ferrochrome was added to the secondary alloyed molten steel to continue refining for 8 min, and samples were taken for testing; when the [Cr] content was 3.01%, the power supply was stopped to obtain refined molten steel and slag; Step 3, the refined molten steel is subjected to vacuum treatment in the VD station. When the vacuum degree is 10kPa-100kPa, the argon blowing amount is 75NL / min; when the vacuum degree is 5kPa-10kPa, the argon blowing amount is increased to 100NL / min; when the vacuum degree is 500Pa-5kPa, the argon blowing amount is increased to 140NL / min; when the vacuum degree is 67Pa-500Pa, the argon blowing amount is increased to 180NL / min; when the vacuum degree is ≤67Pa, the argon blowing amount is first maintained at 230NL / min for 11min and then reduced to 110NL / min for 5min; vacuum-treated molten steel is obtained; Step 4: The vacuum treated molten steel is cast at a constant speed by using secondary cooling combined with electromagnetic stirring of the crystallizer and terminal battery stirring, wherein the primary cooling water flow rate is 4.8m 3 / t, the secondary cooling water flow rate is 0.33m 3 / t, the crystallizer electromagnetic stirring current is 420A, the frequency is 4Hz, the end electromagnetic stirring current is 370A, the frequency is 8Hz, the superheat is 25℃, and the pulling speed is 1.7m / min; the Φ200mm casting billet is obtained; Step 5, the Φ200mm ingot is sent into the annular furnace for heating, and the heating program is set as follows: the preheating section temperature is 900℃, and the holding time is 20min; the heating section temperature is 1200℃, and the holding time is 30min; the heating section temperature is 1220℃, and the holding time is 40min; the heating section temperature is 1250℃, and the holding time is 35min; the soaking section temperature is 1280℃, and the holding time is 25min; the heated ingot is pierced and rolled by a continuous rolling mill, and the length of the concentrated deformation section of the roll in the rolling process is set to 30mm, the feeding angle is 7.0°, the rolling angle is 12.0°, the guide disc speed is 1.55m / s, and the rolled piece linear speed is 0.41m / s; the hot-rolled steel pipe after rolling is subjected to micro-tension reduction, straightened while hot, and air-cooled on a cooling bed, and enters the heat treatment process after passing the flaw detection; Step 6: Send the qualified steel pipe after flaw detection into the heating furnace for quenching treatment, wherein the quenching temperature of the heating section is 810℃, and the heat preservation is 60min, and the quenching temperature of the soaking section is 910℃, and the heat preservation is 16min; after quenching, the steel pipe is water-cooled to 80℃ by external spraying and internal spraying, and then sent to the heating furnace for tempering treatment, wherein the tempering temperature of the heating section is 650℃, and the heat preservation is 30min, the tempering temperature of the heating section is 695℃, and the heat preservation is 25min, and the tempering temperature of the soaking section is 900℃, and the heat preservation is 30min; after tempering, the steel pipe is straightened while hot, and put into the cooling bed for air cooling. After the flaw detection is qualified, the steel pipe is resistant to CO 2 Corrosion of oil casing.

[0046] After testing, the anti-CO2 The raw materials of corroded oil casing include the following chemical components in mass percentage: C: 0.13%, Si: 0.28%, Mn: 0.65%, Cr: 3.01%, Mo: 0.37%, Al: 0.02%, P: 0.006%, S: 0.0011%, [H]: 0.9ppm, [O]: 10ppm, [N]: 52ppm, and the balance is Fe and unavoidable impurities.

[0047] Example 3 This embodiment provides an anti-CO 2 Corroded oil casing and its preparation method, specifically including the following contents: Ingredients: 60.63t of scrap steel, 25.8t of briquettes and 1.5t of graphite balls; The first batch of materials: 23.22t of scrap steel as base, 13.76t of briquettes on top, and 1t of graphite balls on top; The second batch of materials: 19.35t of scrap steel as base, 9.46t of briquettes on top, and 0.5t of graphite balls on top; The third batch of materials: 18.06t of scrap steel as base, and 2.58t of briquettes on top; The carbon content of graphite balls is ≥77%, and the bulk density of each batch is 0.7t / m 3 .

[0048] Step 1, add the first batch of materials into the electric arc furnace, supply power for smelting for 12 minutes, and add 1450kg of lime; when the first batch of materials is 85% melted, add the second batch of materials, continue smelting for 9 minutes, and add 413kg of lime; when the secondary material is 80% melted, add the third batch of materials, and continue smelting for 17 minutes; when the slag basicity is 3.5 and the mass percentage of FeO in the slag is 18%, perform slag flow operation; when the electric furnace temperature is 1635℃ and the mass percentage of [P] in the molten steel is less than 0.005%, tapping is performed under an inert atmosphere; Step 2, under an inert atmosphere, when the steel tapping amount reaches 5%, 41.76 kg of silicon carbide is added to the ladle; when the steel tapping amount reaches 15%, 143.5 kg of aluminum block is added to the ladle; when the steel tapping amount reaches 25%, a chromium-containing alloy is added to the ladle for the first alloying treatment for 50 seconds, and the steel tapping is completed to obtain a primary alloyed steel liquid; wherein the chromium-containing alloy includes the following raw material components in percentage by weight: 55.3% low-carbon ferrochrome, 13.1% high-carbon ferrochrome, 11.2% ferromolybdenum and 20.4% silicon-manganese alloy; Under the inert atmosphere, the primary alloyed steel liquid is sent into the LF refining furnace, and power is supplied. 6.5 kg of aluminum particles and 12.3 kg of calcium carbide are immediately added to the primary alloyed steel liquid for refining for 2 min, and then 1700 kg of low-carbon ferrochrome, 22 kg of aluminum particles, 41.5 kg of calcium carbide and 722 kg of lime are added for further refining for 12 min, and sampling is performed to obtain the secondary alloyed steel liquid; The LF refining furnace was turned on to supply power, and 425 kg of low-carbon ferrochrome was added to the secondary alloyed molten steel to continue refining for 8 min, and samples were taken for testing; when the [Cr] content was 2.93%, the power supply was stopped to obtain refined molten steel and slag; Step 3, the refined molten steel is subjected to vacuum treatment in the VD station. When the vacuum degree is 10kPa-100kPa, the argon blowing amount is 75NL / min; when the vacuum degree is 5kPa-10kPa, the argon blowing amount is increased to 100NL / min; when the vacuum degree is 500Pa-5kPa, the argon blowing amount is increased to 140NL / min; when the vacuum degree is 67Pa-500Pa, the argon blowing amount is increased to 180NL / min; when the vacuum degree is ≤67Pa, the argon blowing amount is first maintained at 230NL / min for 11min and then reduced to 110NL / min for 5min; vacuum-treated molten steel is obtained; Step 4: The vacuum treated molten steel is cast at a constant speed by using secondary cooling combined with electromagnetic stirring of the crystallizer and terminal battery stirring, wherein the primary cooling water flow rate is 4.8m 3 / t, the secondary cooling water flow rate is 0.33m 3 / t, the crystallizer electromagnetic stirring current is 420A, the frequency is 4Hz, the end electromagnetic stirring current is 370A, the frequency is 8Hz, the superheat is 25℃, and the pulling speed is 1.7m / min; the Φ200mm casting billet is obtained; Step 5, the Φ200mm ingot is sent into the annular furnace for heating, and the heating program is set as follows: the preheating section temperature is 720℃, and the holding time is 29min; the heating section temperature is 1150℃, and the holding time is 30min; the heating section temperature is 1280℃, and the holding time is 30min; the heating section temperature is 1220℃, and the holding time is 40min; the soaking section temperature is 1220℃, and the holding time is 30min; the heated ingot is pierced and rolled by a continuous rolling mill, and the length of the concentrated deformation section of the roll in the rolling process is set to 32mm, the feeding angle is 7.0°, the rolling angle is 12.0°, the guide disc speed is 1.55m / s, and the rolled piece linear speed is 0.41m / s; the hot-rolled steel pipe after rolling is subjected to micro-tension reduction, straightened while hot, and air-cooled on a cooling bed, and enters the heat treatment process after passing the flaw detection; Step 6: Send the qualified steel pipe after flaw detection into the heating furnace for quenching treatment, wherein the quenching temperature of the heating section is 830℃, and the heat preservation is 50min, and the quenching temperature of the soaking section is 910℃, and the heat preservation is 18min; after quenching, the steel pipe is water-cooled to 80℃ by external spraying and internal spraying, and then sent to the heating furnace for tempering treatment, wherein the tempering temperature of the heating section is 690℃, and the heat preservation is 20min, the tempering temperature of the heating section is 700℃, and the heat preservation is 30min, and the tempering temperature of the soaking section is 890℃, and the heat preservation is 40min; after tempering, the steel pipe is straightened while hot, and put into the cooling bed for air cooling. After flaw detection, it is resistant to CO 2 Corrosion of oil casing.

[0049] After testing, the anti-CO 2 The raw materials of corroded oil casing include the following chemical components in mass percentage: C: 0.16%, Si: 0.29%, Mn: 0.58%, Cr: 2.93%, Mo: 0.31%, Al: 0.04%, P: 0.006%, S: 0.0013%, [H]: 0.9ppm, [O]: 12ppm, [N]: 48ppm, and the balance is Fe and unavoidable impurities.

[0050] Comparative Example 1 This comparative example provides a CO 2 The difference between the corroded oil casing and the preparation method thereof and Example 1 is that the second step of alloying and refining is carried out in the order of adding slag forming agent-deoxidizing agent-alloy material, and other processes and raw materials remain unchanged and will not be repeated here.

[0051] After testing, the anti-CO 2 The raw materials of corroded oil casing include the following chemical components in mass percentage: C: 0.14%, Si: 0.26%, Mn: 0.61%, Cr: 3.04%, Mo: 0.33%, Al: 0.03%, P: 0.008%, S: 0.0015%, [H]: 0.9ppm, [O]: 12ppm, [N]: 47ppm, and the balance is Fe and unavoidable impurities.

[0052] Comparative Example 2 This comparative example provides a CO 2 The corrosion-resistant oil casing and its preparation method are different from those in Example 1 in that: the anti-CO 2The raw materials of the corroded oil casing include the following chemical components in percentage by mass: C: 0.14%, Si: 0.26%, Mn: 0.61%, Cr: 3.04%, Mo: 0.57%, Al: 0.03%, P: 0.008%, S: 0.0013%, [H]: 0.9ppm, [O]: 15ppm, [N]: 48ppm, and the balance is Fe and unavoidable impurities. Other processes remain unchanged and will not be repeated here.

[0053] Comparative Example 3 This comparative example provides a CO 2 The corrosion-resistant oil casing and its preparation method are different from those in Example 1 in that: the anti-CO 2 The raw materials of the corroded oil casing include the following chemical components in percentage by mass: C: 0.14%, Si: 0.26%, Mn: 0.61%, Cr: 2.61%, Mo: 0.32%, Al: 0.03%, P: 0.006%, S: 0.0013%, [H]: 1.2ppm, [O]: 14ppm, [N]: 45ppm, the remainder is Fe and unavoidable impurities, other processes remain unchanged and will not be repeated here.

[0054] In order to further reflect the technical effect of the present invention, the present invention is to prepare the anti-CO 2 The metallographic structure of the corroded oil casing was tested, and the results are shown in Table 1 and Figure 1-6 As shown; the present invention also obtains the anti-CO 2 Corrosion oil casing and anti-CO obtained in comparative example 1 2 The corroded oil casing was tested for banded structure, and the results are shown in Table 1 and Figure 7-10 shown.

[0055] In order to further demonstrate the technical effect of the present invention, the present invention is to prepare the anti-CO 2 The corrosion resistance test of oil casing and tubing was carried out at 100℃ and P 总气 30MPa, P CO2 Under the condition of 1MPa, the anti-CO 2 The corrosive liquid was flushed on the surface of the corroded oil casing at a flow rate of 1.5m / s for 168h. The contents of the corrosive liquid are as follows: Na + and K + The total amount is 11350 mg / L, Cl - The total amount is 17495 mg / L, HCO 3 - The total amount is 1312 mg / L, SO 4 2- The total amount is 1663 mg / L; the test results are shown in Table 1.

[0056] Table 1 Anti-CO obtained in each embodiment and comparative example 2 Corroded oil casing performance and carbon dioxide corrosion resistance test results

[0057] According to Table 1 and Figure 1-6 It can be seen that the anti-CO provided by the embodiment of the present invention 2 The grain size of the corroded oil casing is relatively high, with good grain size and organizational morphology, which can effectively prevent carbon dioxide pitting. 2 Although the grain size of the corroded oil casing is also in the fine grain range, there is a banded structure, especially in Comparative Example 1. Figure 4 It can be seen that the anti-CO 2 The corroded oil casing steel has obvious banded structure, which can easily lead to problems such as cracking of the steel.

[0058] According to Table 1 and Figure 7-10 It can be seen that the anti-CO provided in Example 1 of the present invention 2 The fewer inclusions in the corroded oil casing indicate that the steel has good crystallinity, which can ensure the continuity of the organization and effectively prevent carbon dioxide from corroding the steel. Figure 8-10 It can be seen that the anti-CO 2 The inclusions in the oil casing steel are seriously corroded, which can easily lead to the reduction of the tensile strength and yield strength of the steel pipe. At the same time, under the impact, the inclusions can easily turn into crack sources, causing brittle fracture of the steel.

[0059] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A CO2 corrosion resistant oil casing, characterized by: The raw materials of the CO2 corrosion resistant oil casing include the following chemical components in percentage by mass: 0.13%≤C≤0.16%, 0.20%≤Si≤0.30%, 0.55%≤Mn≤0.65%, 2.9%≤Cr≤3.1%, 0.3%≤Mo≤0.4%, 0.02%≤Al≤0.04%, P≤0.008%, S≤0.0015%, [H]≤2ppm, [O]≤15ppm, [N]≤60ppm, and the balance is Fe and unavoidable impurities.

2. The preparation process of the CO2 corrosion resistant oil casing according to claim 1, characterized in that: The steps include: The steel-making raw materials are subjected to an electric furnace smelting process, an alloying refining process, a VD vacuum treatment process, and a continuous casting process to obtain a casting billet; the casting billet is sequentially subjected to a heating process, a rolling process, and a heat treatment process to obtain a CO2 corrosion resistant oil casing; The specific operation of the alloying refining process is as follows: in an inert atmosphere, when the molten steel obtained by electric furnace smelting reaches 4%-6%, a pre-deoxidizer is added to the ladle; when the molten steel reaches 14%-16%, a metal deoxidizer is added to the ladle; when the molten steel reaches 24%-26%, a chromium-containing alloy is added to the ladle for the first alloying treatment for 50-60s, and the tapping is completed to obtain a first alloyed molten steel; A diffusion deoxidizer, a low-carbon ferrochrome and a slag-forming agent are sequentially added to the primary alloyed molten steel for secondary alloying treatment to obtain a secondary alloyed molten steel; and the low-carbon ferrochrome in the secondary alloyed molten steel is refined to obtain a refined molten steel and slag.

3. The preparation process of the CO2 corrosion resistant oil casing according to claim 2, characterized in that: The steel tapping endpoint in the electric furnace smelting process is [P]≤0.005%, and the target temperature is 1620℃-1640℃.

4. The preparation process of the CO2 corrosion resistant oil casing according to claim 2, characterized in that: The pre-deoxidizer is silicon carbide; and / or The metal deoxidizer is an aluminum block; and / or The diffusion deoxidizer is aluminum particles and calcium carbide in a mass ratio of 1:1.5-1:2; and / or The chromium-containing alloy comprises the following raw material components in percentage by weight: 54.5%-56.8% low-carbon ferrochrome, 12.3%-13.6% high-carbon ferrochrome, 11.1%-11.4% ferromolybdenum and 19.8%-20.5% silicon-manganese alloy; and / or The carbon content of the low carbon ferrochrome is 0.02%-0.1%; and / or The slagging agent is lime; and / or The mass percentage of Cr2O3 in the slag is 0.1%-0.5%.

5. The preparation process of the CO2 corrosion resistant oil casing according to claim 2 or 4, characterized in that: The mass ratio of the amount of the pre-deoxidizer added to the molten steel is 0.47:1000-0.48:1000; and / or The mass ratio of the added amount of the metal deoxidizer to the molten steel is 1.64:1000-1.65:1000; and / or The mass ratio of the added amount of the chromium-containing alloy to the molten steel is 40.5:1000-44:1000; and / or The mass ratio of the added amount of the low-carbon ferrochrome to the primary alloyed steel liquid is 17:1000-23:1000; and / or The mass ratio of the added amount of the low-carbon ferrochrome to the secondary alloyed steel liquid is 4:1000-6:1000; and / or The mass ratio of the added amount of the diffusion deoxidizer to the molten steel is 0.85:1000-0.95:1000; and / or The mass ratio of the added amount of the slag-forming agent to the molten steel is 8:1000-9:1000.

6. The process for preparing the CO2 corrosion resistant oil casing according to claim 2, characterized in that: The specific operation of the secondary alloying treatment is: power on, immediately add part of the diffusion deoxidizer to the primary alloyed steel liquid for refining for 1 min-2 min, then add low-carbon ferrochrome, the remaining diffusion deoxidizer and slag-forming agent and continue refining for 10 min-12 min, take samples for testing, and obtain the secondary alloyed steel liquid.

7. The process for preparing CO2 corrosion resistant oil casing according to claim 2, characterized in that: In the VD vacuum treatment process, when the vacuum degree is 10kPa-100kPa, the argon blowing amount is 50NL / min-80NL / min; when the vacuum degree is 5kPa-10kPa, the argon blowing amount is 80NL / min-120NL / min; when the vacuum degree is 500Pa-5kPa, the argon blowing amount is 120NL / min-160NL / min; when the vacuum degree is 67Pa-500Pa, the argon blowing amount is 160NL / min-200NL / min; when the vacuum degree is ≤67Pa, first keep the argon blowing amount at 200NL / min-220NL / min for 10min-12min, then reduce the argon blowing amount to 100NL / min-120NL / min and keep it for 3min-5min.

8. The process for preparing CO2 corrosion resistant oil casing according to claim 2, characterized in that: The continuous casting process adopts secondary cooling combined with electromagnetic stirring of the crystallizer and electromagnetic stirring at the end, wherein the flow rate of the primary cooling water is 4.6m 3 / t-5.1m 3 / t, the secondary cooling water flow rate is 0.32m 3 / t-0.34m 3 / t, the crystallizer electromagnetic stirring current is 400A-450A, the frequency is 3Hz-5Hz, the end electromagnetic stirring current is 350A-400A, the frequency is 7Hz-9Hz, the superheat is 20℃-25℃, and the pulling speed is 1.5m / min-2.1m / min.

9. The process for preparing CO2 corrosion resistant oil casing according to claim 2, characterized in that: The heating procedure of the heating process is as follows: the temperature of the preheating section is 700°C-900°C, and the holding time is 20min-30min; the temperature of the first heating section is 900°C-1200°C, and the holding time is 30min-40min; the temperature of the second heating section is 1200°C-1280°C, and the holding time is 30min-40min; the temperature of the third heating section is 1220°C-1300°C, and the holding time is 30min-40min; the temperature of the soaking section is 1220°C-1290°C, and the holding time is 20min-30min; and / or The rolling process includes a piercing process, a rolling process, a diameter reduction process, a cooling bed process, a straightening process and a flaw detection process in sequence; wherein, in the rolling process, the length of the concentrated deformation section of the roll is 28mm-32mm, the feed angle is 6.9°-7.1°, the rolling angle is 11.8°-12.2°, the guide plate speed is 1.5m / s-1.6m / s, and the linear speed of the rolled piece is 0.40m / s-0.42m / s; and / or The heat treatment includes quenching, water cooling, tempering, straightening, air cooling and flaw detection in sequence; wherein the quenching temperature is 810°C-910°C, and the tempering temperature is 650°C-708°C.

10. The process for preparing CO2 corrosion resistant oil casing according to claim 9, characterized in that: During the quenching operation, the quenching temperature of the heating section is 810°C-850°C, and the quenching and holding time of the heating section is 35min-60min; the quenching temperature of the soaking section is 890°C-910°C, and the quenching and holding time of the soaking section is 16min-24min; and / or During the tempering operation, the tempering temperature of the first heating stage is 650℃-690℃, and the tempering holding time of the first heating stage is 20min-30min; the tempering temperature of the second heating stage is 688℃-708℃, and the tempering holding time of the second heating stage is 15min-30min; the tempering temperature of the soaking section is 890℃-910℃, and the tempering holding time of the soaking section is 30min-40min.